Peran Perpustakaan Desa Balai Buntar Bengkulu Tengah Dalam Pengembangan Literasi Informasi Masyarakat Pondok Kelapa - Putri, Deny; Samosir, Fransiska Timoria; Sa’diyah, Lailatus (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The Role of the Balai Buntar Village Library, Central Bengkulu in Developing Information Literacy in the Pondok Kelapa Community. Using qualitative methodology, this research examines the important impact of the Village Library's role in collecting data through observation, document analysis and interviews. The findings of this research highlight the efforts made by libraries to provide information accessibility, implement information literacy programs, empower the community, utilize technology, collaborate and build community creativity, as well as monitor and evaluate library operations. These results provide a comprehensive understanding of the benefits and role of the Village Library for the Pondok Kelapa Community as a center for community information literacy and also know that programs such as training, interest in reading, and collaboration/cooperation carried out with educational institutions are the key to success in improving information literacy skills.Â